Effects of multisession transcranial direct current stimulation as an augmentation to cognitive tasks in patients with neurocognitive disorders in Japan: a study protocol for a randomised controlled trial. Issue 12 (23rd December 2020) - Inagawa, Takuma; Yokoi, Yuma; Yamada, Yuji; Miyagawa, Nozomi; Otsuka, Takeshi; Yasuma, Naonori; Omachi, Yoshie; Tsukamoto, Tadashi; Takano, Harumasa; Sakata, Masuhiro; Maruo, Kazushi; Matsui, Mie; et al.
Abstract : Introduction: Transcranial direct current stimulation (tDCS) is a potentially novel strategy for cognitive enhancement in patients with disorders. We present a study protocol for a randomised controlled trial designed to evaluate the safety and efficacy of tDCS combined with cognitive tasks on cognition in such patients. Method and analysis: This is a two-arm, parallel-design, randomised, sham-controlled trial, in which participants and raters will be blinded at a single centre. Stratified randomisation will be conducted, and a randomisation sequence will be generated through the Electronic Data Capture system. Patients who met the Diagnostic and Statistical Manual of Mental Disorders-5 criteria for neurocognitive disorders will be recruited and randomised to receive either active (2 mA for 20 min) or sham (stimulation ramped up and down for 1 min) stimulation in 10 sessions over five consecutive days. A direct current will be transferred by a 35 cm 2 saline-soaked sponge electrode. An anode will be placed over the left dorsolateral prefrontal cortex, and a cathode will be placed over the right supraorbital cortex. Calculation tasks will be conducted in both arms as a cognitive task for 20 min during the stimulation. This task consists of basic arithmetic questions, such as single-digit addition, subtraction, multiplication and division. The primary outcome will be the mean change in the Alzheimer Disease Assessment Scale–cognition at Day 5 after baseline. Depressive symptoms, as measured by the geriatric depression scale, and quality of life, as measured by the Medical Outcomes Study 36-item Short-Form Health Survey, will also be assessed. Data will be collected at baseline, within 3 days following the final stimulation and 1 month thereafter. The estimated sample size is 46 per group based on the assumptions that an estimated mean difference is −1.61 and SD is 2.7. Mixed models for repeated measures will be used for the statistical analysis. Ethics and dissemination: The National Center of Neurology and the Psychiatry Clinical Research Review Board (CRB3180006) approved this study. The results of this study will be published in a scientific peer-reviewed journal. Trial registration details: Japan Registry of Clinical Trials jRCTs032180016.